2015
DOI: 10.1111/bjet.12303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a peer competition‐based mobile learning approach on students' affective domain exhibition in social studies courses

Abstract: One of the important and challenging objectives of social studies courses is to promote students' affective domain exhibition, including learning interest, positive attitudes and local culture identity. In this paper, a location-aware mobile learning approach was proposed based on a competition strategy for conducting local cultural activities in the field. During the field trip, the learners were asked to learn in the mobile learning environment by throwing a dice to determine their moves using a tablet compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…The study examined their construct validity, internal consistency reliability, and interrater reliability as a guideline for digital game story designers and product developers to modify creative and entertaining game stories. In terms of Contextual mobile learning, Hwang and Chang (2016) presented a location-aware mobile learning way using the contest strategy to conduct local culture activities in social studies class. The findings showed that this measure largely enhanced students' local culture identity, learning interest, and learning attitude, and that it also decreased students' cognitive load.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…The study examined their construct validity, internal consistency reliability, and interrater reliability as a guideline for digital game story designers and product developers to modify creative and entertaining game stories. In terms of Contextual mobile learning, Hwang and Chang (2016) presented a location-aware mobile learning way using the contest strategy to conduct local culture activities in social studies class. The findings showed that this measure largely enhanced students' local culture identity, learning interest, and learning attitude, and that it also decreased students' cognitive load.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…The core benefits of mobile devices, such as unlimited mobility, flexibility, and small size, are capable of introducing new opportunities for improving the learning environments in different forms, such as the engagement of users with mobile devices by assuming that students are constantly moving from one place to another, a dynamic process of developing skills and knowledge through training among peers, and learning taking place even in informal settings. Beside of supporting traditional face-face instruction, mobile learning solutions through the appropriate knowledge creation and distribution can also stimulate invention, as well teaching and learning approaches based on knowledge creation and distribution, such as social learning (Huang et al, 2010;Oyelere et al, 2016c), inquiry-based learning (Jones et al, 2013;Shih et al, 2010), blended learning (Minjuan et al, 2009), flipped learning , online distance learning (Rekkedal and Dye, 2007), game-based learning (Klopfer et al, 2012;Su and Cheng, 2015), cooperative learning (Roschelle et al, 2010), collaborative learning (Kukulska-Hulme and Shield, 2008), competition-based learning (Hwang and Chang, 2015), active learning (Laurillard, 2007), and exploratory learning (Liu, 2012). Consequently, mobile devices and wireless technology have the prospects of introducing cutting-edge innovations in education, especially the aspect of teaching methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The peering or neighbouring approach leads productive social interaction, responsiveness, cooperation and positive attitudes and social harmony. It supports learning environment and encouraging participation in interaction (48). A systematic review shows that adolescents and sexuality health education had improved in knowledge, attitude and intentions by peer leading approach (49).…”
Section: Characteristics Of Respondents and Householdsmentioning
confidence: 99%